Percutaneous endoscopic interlaminar discectomy for L5-S1 calcified lumbar disc herniation: A retrospective study - Cheng, Yuanpei; Zhang, Qianru; Li, Yongbo; Chen, Xipeng; Wu, Han (Frontiers in Surgery, 2022)
Background: Calcified lumbar disc herniation (CLDH) is considered to be a special type of lumbar disc herniation (LDH). Percutaneous endoscopic interlaminar discectomy (PEID), with safety and efficacy, has been proved to be a minimally invasive surgery for LDH. However, there are few studies on PEID in the treatment of CLDH at L5-S1 level. This research aimed to analyze the clinical efficacy of PEID for L5-S1 CLDH. Methods: From August 2016 to April 2020, we retrospectively analyzed 28 consecutive patients (17 males; 11 females) with L5-S1 CLDH treated with PEID at our institution. All the patients were followed up for greater than 1 year postoperatively. The demographic characteristics, surgical results and clinical outcomes estimated by the visual analog scale (VAS) for leg pain, Oswestry disability index (ODI) and modified MacNab criteria were collected. Results: All patients were successfully performed by PEID. The mean operative time and intraoperative blood loss were 65.36 ± 5.26 minutes and 13.21 ± 4.35 ml, respectively. The VAS for leg pain and ODI scores improved remarkably from 7.54 ± 0.96 to 1.50 ± 0.51 (P < 0.05) and from 69.29 ± 9.91 to 17.43 ± 3.69 (P < 0.05) a year after operation, respectively. According to the modified MacNab criteria of the last follow-up, the excellent and good rates are 92.86%. Two of the patients had complications, one had nerve root injury and the other had postoperative dysesthesia. Conclusions: PEID achieved good clinical outcomes in the treatment of L5-S1 CLDH. And PEID was a safe and effective minimally invasive surgery for L5-S1 CLDH.